2012
DOI: 10.7326/0003-4819-156-4-201202210-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Systematic Family History Enquiry to Cardiovascular Disease Risk Assessment in Primary Care

Abstract: Genetics Health Services Research program of the United Kingdom Department of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 41 publications
4
73
0
Order By: Relevance
“…12, 28 The results of this pilot trial suggest that each of the three electronic portals has the capacity to increase the availability of valid family health history in the EHR.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…12, 28 The results of this pilot trial suggest that each of the three electronic portals has the capacity to increase the availability of valid family health history in the EHR.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3][4][5][6][7] Electronic tools for patients may facilitate the collection of these data so that providers have more time to discuss preventive health care consequences. 8 Several factors are converging to drive interest in the adoption of effective and efficient systems for obtaining electronic data for family history from patients, including financial incentives for the "meaningful use" of electronic health records (EHRs), 9 new evidence for the clinical utility of family history, 10 and the growing use of genomics. 11 A recent report by Qureshi confirmed that adding family history improves the identification of persons with high cardiovascular risk in primary care practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 One study did show that automated collection of family history can identify more patients at risk for heart disease, but it did not go on to demonstrate improved patient care outcomes from the availability of such information. 47 More studies that examine the clinical utility of family history, including the best way to engage PCPs in using this information are needed before we begin to use automated prompts and alerts for high-risk family histories.…”
Section: Resultsmentioning
confidence: 99%
“…The ADDFAM (Added Value of ADDing FAMily History) cluster randomised trial, set in England, has recently demonstrated the utility of adding systematic family history enquiry to primary care cardiovascular disease risk assessment. 24,25 Other studies have also suggested that simple tools can correctly identify the majority of people with a significant family history of coronary heart disease or diabetes, 26 or colorectal cancer, 27 when compared with a detailed questionnaire. Using brief questionnaires to identify people at higher risk of other diseases such as depression has been established primary care practice for some time.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%